(untitled) (Bangladesh Journal of Medicine, 2021)
Guillain-Barre syndrome (GBS) following typhoid is extremely uncommon and only few case reports are available in literature. The importance of this case report is to highlight upon the fact that a diagnosis of GBS should always be kept in mind whenever a patient of typhoid fever develops weakness. We report a young girl with blood culture proven typhoid fever that developed this very rare neurological complication quite early in the course of the disease. Following treatment with intravenous antibiotics and intravenous immunoglobulin, she was improved. Bangladesh J Medicine July 2021; 32(2) : 142-144